2014
DOI: 10.1021/ie503421f
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Phytic Acid Polyelectrolyte Complex: A Green and Renewable Intumescent Flame Retardant System for Ethylene–Vinyl Acetate Copolymer

Abstract: We describe the preparation and characterization of a green and renewable polyelectrolyte complex (PEC) containing phosphorus, nitrogen and carbon elements, based on the ionic complexation between chitosan and phytic acid. Introduction of this PEC to ethylene−vinyl acetate copolymer (EVA) leads to an improvement of the flame retardancy. As for the EVA/PEC composites with 20.0 wt % of PEC (EVA/20PEC), the char residue at 600°C is 12 wt % higher than that of the pristine EVA under nitrogen atmosphere. Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(91 citation statements)
references
References 48 publications
0
91
0
Order By: Relevance
“…The objective of this work is to study the effect of different metallic phytate salts as biosourced phosphorous flame retardant additives for PLA. Few studies reported the use of phytic acid or salts in combination with other flame retardant additives [42][43][44][45][46] but not as a unique FR agent. The literature on this subject is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work is to study the effect of different metallic phytate salts as biosourced phosphorous flame retardant additives for PLA. Few studies reported the use of phytic acid or salts in combination with other flame retardant additives [42][43][44][45][46] but not as a unique FR agent. The literature on this subject is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , the XRD pattern of PLA shows typical peaks at around 14.1°, 17.1°, 18.6°, and 25.7°, respectively, which are ascribed to the α‐form crystals . In the case of BOZ, there are two broad peaks over the range of 5°–30°, demonstrating its amorphous structure . After adding BOZ to PLA, little changes in diffraction intensity can be found for the four typical peaks of PLA.…”
Section: Resultsmentioning
confidence: 97%
“…Chitosan (CS) is a linear aminopolysaccharide derived from chitin, a major component of insects and crustacean shells [26]. Tao Zhang et al [27] designed a novel CS based polyelectrolyte complex (PEC) containing phosphorus, nitrogen and carbon elements.…”
Section: Polysaccharidesmentioning
confidence: 99%